Hematological safety of perinatal exposure to zidovudine in uninfected infants born to HIV type 1-infected women in Thailand - Nelly Briand (2018)
The evolution of hematological parameters in HIV-1-exposed uninfected infants according to various durations of perinatal zidovudine exposure was studied. We used data prospectively collected among 1122 HIV-uninfected formula-fed infants born to HIV-infected mothers who participated in a clinical trial to prevent perinatal transmission in Thailand (PHPT-1). Infants were exposed to different durations of zidovudine both in utero and after birth. Hemoglobin level and leukocyte, absolute neutrophil, and lymphocyte counts were measured at birth and at 6 weeks of age. The association between hematological parameters at birth and the duration of zidovudine exposure in utero was studied using a linear regression model, and changes between birth and 6 weeks of age and the duration of postnatal zidovudine exposure using mixed effects models. At birth, the hemoglobin level was lower in newborns exposed to zidovudine for more than 7.5 weeks in utero (adjusted regression coefficient: -0.6g/dl; 95% confidence interval: -1.1 to -0.1). Six weeks after birth, the hemoglobin level had decreased faster in infants administered zidovudine for more than 4 weeks (adjusted regression coefficient: -0.1 g/dl; 95% confidence interval: -0.2 to -0.1). The duration of perinatal zidovudine exposure was not associated with the evolution of leukocyte, neutrophil, and lymphocyte counts. Despite the differences in hemoglobin levels, grade 3 or 4 anemia did not significantly differ by maternal or infant zidovudine duration. The clinical impact appeared modest, but longer exposure may warrant close monitoring. Copyright 2010, Mary Ann Liebert, Inc.